Preparation method and application of high-power Prussian blue material

By controlling the crystallization precipitation method and particle suppression agglomeration treatment, optimizing the stirring equipment and precipitation process, the problems of unshortened particle size distribution and serious agglomeration in high-power batteries are solved, and a single high-power Prussian blue material is realized Dispersed narrow particle size distribution and excellent electrochemical properties.

CN119461415APending Publication Date: 2025-02-18XIAMEN THREE CIRCLES BATTERY CO LTD
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411439464.2
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-10-15
Publication Date
2025-02-18

AI Technical Summary

Technical Problem

The existing Prussian blue materials have problems such as unshort particle size distribution and serious agglomeration between particles in high-power battery applications, resulting in a decrease in battery cell capacity and a decrease in voltage platform, limiting the application of sodium ion batteries in ultra-high power scenarios.

Method used

By using the controlled crystal precipitation method, the number of nucleation and surface charge adsorption during the precipitation process is optimized, and the particle suppression agglomeration treatment is carried out through steps such as aging and airflow crushing. High-power Prussian blue material with narrowed particle size distribution and uniform dispersion between particles.

Benefits of technology

Achieve the monodispersed narrow particle size distribution of high-power Prussian blue materials, reduce secondary agglomeration between particles, improve the specific surface area and electrochemical performance of the material, and maintain 70% of 1C at a discharge rate of ≥60C. Capacity of more than % is better than traditional agglomeration form positive electrode materials.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119461415A_ABST
    Figure CN119461415A_ABST
Patent Text Reader

Abstract

The invention discloses a preparation method and application of a high-power Prussian blue material, and belongs to the field of battery materials.The preparation method of the high-power Prussian blue material comprises the following steps that S1, a solution containing ferrocyanide is prepared to serve as a raw material A, and a solution containing transition metal salt is prepared to serve as a raw material B; s3, laser particle size distribution detection is conducted in the precipitation process, a particle growth speed curve graph is made according to the detected particle size distribution D50 value, when an upward inflection point appears on the curve and the slope is larger than 1, zeta potential detection is conducted, and when the zeta potential is detected to range from-25 mV to-30 mV, the particle growth speed curve graph is obtained. And S4, continuously carrying out precipitation treatment after particle agglomeration inhibition treatment, washing and drying to obtain the high-power Prussian blue material, primary particles are uniformly dispersed, and secondary agglomeration between the particles is reduced.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention belongs to the field of battery materials, and in particular relates to a preparation method and application of a high-power Prussian blue material. Background Art

[0002] Prussian blue-based cathode materials are expected to achieve excellent rate performance when used as cathode materials for sodium-ion batteries due to their unique three-dimensional framework structure, which is conducive to the rapid insertion and extraction of sodium ions. However, the performance of Prussian blue-based aggregate materials deteriorates sharply after the charge and discharge rate of the battery cell exceeds 40C. Due to increased polarization and other reasons, the battery cell capacity is reduced to less than 10% of the initial capacity and the voltage platform is reduced to below 2V, which limits the application of sodium-ion batteries in certain ultra-high power scenarios.

[0003] On the other hand, we also found in the pilot and trial production process that with the scale-up of the reaction equipment, especially the mixing effect of the reactor above 300L is quite different from the reactor below 1L commonly used in the laboratory. Due to the existence of some areas with poor mixing effect, a large amount of Prussian blue is prone to inter-particle agglomeration (including soft agglomeration or hard agglomeration) due to interactions such as van der Waals force, electrostatic force or hydrogen bond, especially when the particle size is greater than 1.5μm, the agglomeration is aggravated, and the specific surface area of ​​the material is also rapidly reduced. In high-power batteries, the specific surface area of ​​the particles is required to be large, and the particle size distribution is narrowed. Therefore, in this application scenario, it is necessary to try to avoid secondary agglomeration between primary particles. At the same time, monodispersed single crystal particles have better crystallinity and fewer defects, and their gram capacity can also be improved accordingly. However, the Prussian blue materials synthesized by the existing large-scale co-precipitation technology will show more or less agglomeration. During the precipitation process, the particle growth rate suddenly increases, and the primary particles continue to grow in secondary clusters. On the one hand, this shortens the precipitation time and reduces the output. On the other hand, the changes in particle size and specific surface area become more unpredictable, and the detection frequency needs to be increased. Otherwise, unqualified products will easily appear. Summary of the invention

[0004] The purpose of the present invention is to provide a method for preparing a high-power Prussian blue material and its application, so as to overcome at least one of the above-mentioned defects in the prior art.

[0005] To achieve this object, the present invention adopts the following technical solutions:

[0006] The invention provides a method for preparing a high-power Prussian blue material, comprising the following steps: S1: preparing a solution including ferrocyanide as a raw material A, preparing a solution including a transition metal salt as a raw material B, S2: adding a base liquid into a container, introducing nitrogen into the container, and continuously adding the raw material A and the raw material B into the base liquid after 2-6 hours, stirring and mixing to form a precipitate, S3: performing laser particle size distribution detection during the precipitation process, making a particle growth rate curve according to the detected particle size distribution D50 value, when the curve has an upward inflection point and the slope is greater than 1, or performing zeta potential detection, when the detected zeta potential is between -25mV and -30mV, performing a particle agglomeration inhibition treatment, S4: continuing the particle agglomeration inhibition treatment after the particle agglomeration inhibition treatment, until the detected particle size distribution D50 is 1.0-6.0μm, stopping the feeding, and obtaining the high-power Prussian blue material after washing and drying.

[0007] Preferably, the particle size distribution of the high-power Prussian blue material is D50=1.0-6.0 μm, more preferably, D50=2.0-5.0 μm, the particle size distribution is unimodal, the particle size span is ≤1.20, more preferably, the particle size span is ≤1.00, and BET is ≥2.0 m 2 / g, preferably, BET is 3.0-10.0m 2 / g.

[0008] Preferably, raw material A includes at least one of sodium ferrocyanide aqueous solution, potassium ferrocyanide aqueous solution, and lithium ferrocyanide aqueous solution, with a molar concentration of 0.1-1 mol / L, and the temperature of raw material A is 20-60°C. Raw material B includes one or more mixed solutions of sulfates of manganese, iron, cobalt, nickel, zinc, and copper, with a molar concentration of 0.1-3 mol / L. The base liquid is an aqueous solution, a sodium sulfate solution, or a sodium chloride solution, and the mass concentration of the sodium sulfate solution or the sodium chloride solution is 100-300 g / L. The temperature of the base liquid is 0°C-40°C. The base liquid also includes a complexing agent with a mass concentration of 30-300 g / L. More preferably, the mass concentration of the complexing agent is 150-250 g / L, and the complexing agent is trisodium citrate, ammonia water, sodium oxalate, sodium phosphate, sodium pyrophosphate , sodium acetate, ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetate, sodium manganese ethylenediaminetetraacetate, triethanolethylenediamine, urea, sodium succinate, sodium tartrate, polyvinylpyrrolidone, and polyacrylamine. In step S2, after the base liquid is added to the container, an inorganic dispersant containing sodium ions or an organic surfactant dispersant is added to the base liquid, and the amount of the dispersant added is 0.02-1% of the mass of the base liquid. The inorganic dispersant containing sodium ions is at least one of sodium silicate, sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate, and sodium aluminate. The organic surfactant dispersant is at least one of long-chain fatty acids, hexadecyltrimethylammonium bromide, triethylhexyl phosphoric acid, sodium dodecyl sulfate, methylpentanol, polyacrylamide, fatty acid polyethylene glycol ester, and polyether siloxane.

[0009] Preferably, the container in step S2 is a reactor, the volume of the reactor is greater than 300L, the reactor has a stirrer, the number of stirring paddle layers of the stirrer is ≥2, the stirring blade is a paddle-type or propeller-type blade with an inclination angle of greater than 30°, the length-to-diameter ratio of the stirring blade is greater than 5, more preferably, the length-to-diameter ratio of the stirring blade is 8-12, the reactor has a guide tube inside, the guide tube is sleeved on the outside of the stirring paddle, and the stirring blade of the lowest layer is flush with the bottom of the guide tube, the bottom of the reactor is in an arc shape, and the center of the bottom wall of the reactor is The device is provided with a protrusion, the motor power of the agitator is greater than 60kw, more preferably, the motor power of the agitator is 75kw, the maximum speed of the stirring paddle is greater than 200rpm, more preferably, the maximum speed of the stirring paddle is 250-350rpm, the time for raw material A, raw material B, and bottom liquid to be evenly mixed in the reactor is less than 1s, more preferably, the time for raw material A, raw material B, and bottom liquid to be evenly mixed in the reactor is 0.2-0.3s, and the feed rate of raw material A and raw material B is 40-200L / h.

[0010] Preferably, in the precipitation reaction, the precipitation synthesis temperature is 0-40°C, more preferably, the precipitation synthesis temperature is 15-30°C, the solid content is 0-10%, more preferably, the solid content is 5-8%, the precipitation period is 3-12h, more preferably, the precipitation period is 4-10h, in 0-1h of the precipitation reaction, the stirring line speed is >500cm / s, more preferably, the stirring line speed is 600-800cm / s, after 1h of the precipitation reaction, the stirring line speed is <500cm / s, after 1h of the precipitation reaction, the particle size is controlled to be 20-30% of the target particle size, if the particle size is <20% of the target particle size, part of the slurry is discharged immediately, in the precipitation reaction, when the solid content is >10%, part of the slurry is discharged and concentrated, and the concentrated liquid obtained is returned to the container for dilution to reduce the solid content.

[0011] Preferably, before laser particle size distribution detection, the slurry is taken out from the container and ultrasonically treated for 5-8 min at an ultrasonic power of 20-100 KHz, more preferably, at an ultrasonic power of 50-80 KHz, or the taken out slurry is filtered and washed, and dried at 100-120° C. for 10-20 min.

[0012] Preferably, in step S3, a particle growth rate curve is prepared with the precipitation time as the horizontal coordinate and the particle volume change as the vertical coordinate, and the particle volume change at the n+1 hour compared to the n hour is calculated as follows: [(D50(n+1) / 2) 3 -(D50(n) / 2) 3 ] / [(n+1)-n].

[0013] Preferably, the particle agglomeration inhibition treatment includes at least one of oxidizing the particle surface, increasing the pH value of the precipitation process, and circulating the slurry. In step S4, aging is carried out after stopping the feeding, nitrogen is introduced during the aging process and the slurry is circulated. After aging for 4-8 hours, washing and drying are carried out to obtain a high-power Prussian blue material. The high-power Prussian blue material obtained in step S4 is also subjected to air flow crushing treatment, and the grading frequency of the air flow crushing is 25-40Hz, and the crushing pressure is 0.3-1.2Mpa. More preferably, the crushing pressure is 0.4-0.6Mpa.

[0014] Preferably, the oxidation treatment of the particle surface includes introducing compressed air, pure oxygen or hydrogen peroxide into the container at a flow rate of 100-300 L / h and an oxidation time of 10-120 min. More preferably, the oxidation time is 10-60 min. Increasing the pH value of the precipitation process includes adding at least one of sodium hydroxide, sodium carbonate, sodium oxalate, potassium hydroxide, potassium hydroxide and potassium oxalate into the container to control the pH value at 7.5-8.0. The circulation treatment of the slurry includes continuously discharging the slurry from the bottom of the container and continuously feeding the discharged slurry into the container from the top of the container through a diaphragm pump, and the pressure of the diaphragm pump is 0.1-0.8 MPa.

[0015] The present invention also provides the use of the high-power Prussian blue material prepared by the above-mentioned high-power Prussian blue material preparation method in the preparation of sodium ion batteries.

[0016] The beneficial effects of the present invention are:

[0017] By strengthening and optimizing the dispersion, mixing and shearing effects of the stirring equipment during the precipitation process, regulating the number of nuclei and surface charge adsorption during the precipitation synthesis process, and aging and secondary crushing of the materials after the synthesis, the Prussian blue positive electrode material with uniform dispersion between primary particles, reduced secondary agglomeration between particles, and narrow particle size distribution is obtained. In the production scale-up, monodisperse narrow particle size distribution particles with consistent physicochemical properties with the pilot test were obtained, laying the foundation for the large-scale application of high-power Prussian blue. The sodium ion battery assembled with the prepared high-power Prussian blue material as the positive electrode material can achieve a discharge rate of ≥60C, and the capacity retention rate is more than 70% at a rate of 1C. The controlled crystallization precipitation method is used to synthesize monodisperse narrow particle size distribution Prussian blue particles, the number of secondary agglomerates between particles is reduced, and the specific surface area of ​​the material is increased, thereby shortening the diffusion path of sodium ions from the surface of the particles to the inside, increasing the contact area between the material surface and the sodium ion electrolyte, and improving the ultra-high rate discharge capacity of the sodium ion battery, which is superior to the traditional agglomerated positive electrode material. During the synthesis process, the particle agglomeration situation can be quantitatively determined in real time through rapid detection methods such as the color control of the reactor slurry, the distinction between soft and hard agglomeration of particles, the particle size growth rate curve, and zeta potential analysis, so as to adjust and optimize the precipitation process in time. These control processes and detection methods can also be extended to the synthesis process of other monodisperse battery material systems. BRIEF DESCRIPTION OF THE DRAWINGS

[0018] Figure 1 It is a graph showing the particle size change and particle growth rate of Example 1 of the present invention and Comparative Example 1.

[0019] Figure 2 This is the color comparison card for the oxidation process of Example 1 of the present invention (the box is the qualified color area after oxidation).

[0020] Figure 3 It is an electron microscope image and a schematic diagram of the structure of Example 1 of the present invention (upper right corner).

[0021] Figure 4 It is the electron microscope image and structural schematic diagram (upper right corner) of comparative example 1 of the present invention.

[0022] Figure 5 It is a graph showing the change in particle size distribution of Example 1 of the present invention and Comparative Example 1.

[0023] Figure 6 It is a comparison diagram of the XRD diffraction spectra of Example 1 of the present invention and Comparative Example 1.

[0024] Figure 7 It is a charge and discharge curve diagram of Example 1 of the present invention and Comparative Example 1 at a 10C rate.

[0025] Figure 8 It is a schematic diagram of the structure of the reactor of Example 2 of the present invention.

[0026] Fig. 9 It is an electron microscope image of the finished product of Example 2 of the present invention.

[0027] Fig.10 It is the electron microscope picture of the finished product of comparative example 2 of the present invention.

[0028] Fig.11 It is a comparison diagram of the particle size distribution of the high-power Prussian blue material before and after air flow crushing in Example 3 of the present invention.

[0029] Fig.12 This is a particle size distribution diagram of the high-power Prussian blue material after air flow crushing in Comparative Example 3 of the present invention.

[0030] Fig.13 This is an electron microscope image of the high-power Prussian blue material after air flow crushing in comparative example 3 of the present invention.

[0031] Fig.14 It is a discharge curve diagram of the soft-pack battery assembled with high-power Prussian blue materials in Example 3 of the present invention at 1C and 60C rates.

[0032] The markings in the accompanying drawings are: 1-reactor, 2-agitator, 3-stirring blades, 4-guide tube, 5-protrusion. DETAILED DESCRIPTION

[0033] The present invention will now be further described with reference to the accompanying drawings and specific implementation methods.

[0034] Contents not described in detail in this specification belong to the prior art known to professional and technical personnel in this field. In the description of the present invention, it should be understood that the orientation or position relationship indicated by the terms "center", "upper", "lower", "front", "back", "left", "right", "vertical", "horizontal", "top", "bottom", "inner", "outer", "clockwise", "counterclockwise", etc. are based on the orientation or position relationship shown in the drawings, which is only for the convenience of describing the present invention and simplifying the description, rather than indicating or implying that the device or element referred to must have a specific orientation, be constructed and operated in a specific orientation, and therefore cannot be understood as limiting the present invention. In addition, the terms "first", "second", "third", etc. are only used to distinguish the description, and cannot be understood as indicating or implying relative importance.

[0035] Embodiment 1:

[0036] The method for preparing a high-power Prussian blue material provided in this embodiment specifically relates to a method for preparing a monodisperse narrow particle size distribution Prussian blue positive electrode material for a sodium ion battery, comprising the following steps:

[0037] S1: Prepare a sodium ferrocyanide aqueous solution ((Na4Fe(CN)6)) with a molar concentration of 0.2 mol / L as raw material A, the temperature of raw material A is 20°C, prepare a mixed solution of manganese sulfate (MnSO4) and ferrous sulfate (FeSO4) with a molar concentration of 0.2 mol / L as raw material B, wherein the Mn:Fe (molar ratio) is 4:1.

[0038] S2: Add 100L ultrapure water and 20Kg trisodium citrate complexing agent as the base liquid to the 500L reactor 1. The base liquid temperature is 30℃. Add 30g sodium silicate dispersant to the base liquid. The dispersant changes the surface properties of the particles, thereby changing the interaction between the particles and the liquid medium, and between the particles, and increasing the repulsion between the particles. The sodium silicate dispersant dissociates and becomes charged in the aqueous solution. Adsorption to the surface of the powder can increase the surface potential of the particles, increase the electrostatic repulsion between the particles, and sodium ions will not introduce other metal impurities. The precipitation synthesis temperature is 30℃. When it exceeds 40℃, the particles are prone to secondary agglomeration. Reactor 1 needs to be equipped with cooling circulating water and a water bath jacket for cooling and temperature control. Nitrogen is introduced into reactor 1. After 2h, raw materials A and B are continuously added to the base liquid respectively. The feed rate of raw materials A and B is 200L / h, and they are stirred and mixed to form a precipitate. During the 0-1h of the precipitation reaction, in order to meet the precipitation cycle and solid content requirements, a large amount of nucleation is required in the initial stage of the reaction (0-1h), and the stirring line speed is greater than 500cm / s. The stirring line speed of this embodiment is 800cm / s. After 1h of precipitation reaction, D50=1.125μm. In order to reduce the number of crystal nuclei, the stirring line speed is reduced to 300cm / s to prevent violent collisions between particles and agglomeration.

[0039] Among them, the reactor 1 has an agitator 2, the number of stirring paddle layers of the agitator 2 is 2, the stirring blade 3 is a propulsion blade with an inclination angle of 45°, and the length-to-diameter ratio of the stirring blade 3 is 8. The reactor 1 has a guide tube 4 inside, which is sleeved on the outside of the stirring paddle. The setting of the guide tube 4 enhances the uniformity of material mixing, stabilizes the circulation flux, and enhances the normal distribution of particle size. And the stirring blade 3 of the lowest layer is flush with the bottom of the guide tube 4, so as to take into account dispersion, shearing and circulation. The bottom of the reactor 1 is in an arc shape to reduce the dead angle area of ​​material mixing. And a protrusion 5 is provided at the center of the bottom wall of the reactor 1 to enhance the reflux effect and make it difficult to form a vacuum area at the bottom. The motor power of the agitator 2 is 75kw, the maximum speed of the stirring paddle is 250rpm, and the time for raw material A, raw material B, and bottom liquid to be evenly mixed in the reactor 1 is 0.2s. The raw materials are added to the reactor 1 by quantitative dropwise addition. The equipment used for addition is a peristaltic pump, a metering pump, a screw pump, and the flow control equipment is an electromagnetic flowmeter, a rotor flowmeter, a vortex flowmeter, a valve, etc.

[0040] S3: Laser particle size distribution detection is performed every hour during the precipitation process. Before the laser particle size distribution detection is performed, the slurry is taken out of the container. The agglomeration of particles in the slurry is generally divided into soft agglomeration and hard agglomeration. Soft agglomerate particles will not disperse during conventional particle size testing, but will disperse again after the material is washed and dried to remove water (hard agglomerates will not disperse). Therefore, the soft agglomeration phenomenon will cause misjudgment of the actual particle size and particle distribution. In order to avoid misjudgment, the removed slurry is treated with external ultrasound and internal ultrasound for 8 minutes, and the ultrasonic power is 80KHz. A particle growth rate curve is prepared based on the D50 value of the particle size distribution detected every hour. Specifically, because the product is a cube, the particle growth rate curve is prepared with the precipitation time as the horizontal coordinate and the particle volume change as the vertical coordinate. The calculation formula for the particle volume change in the n+1 hour compared to the n hour is: [(D50(n+1) / 2) 3 -(D50(n) / 2) 3 ] / [(n+1)-n]. When the curve has an upward inflection point and the slope is greater than 1, it indicates that the particles are rapidly agglomerating and growing. At this time, the precipitation process needs to be adjusted to suppress the secondary agglomeration of particles. Specifically, after 3 hours of precipitation, it is found that the particle growth rate curve has an upward inflection point and the slope is greater than 1 ( Figure 1 ), at this time, compressed air is introduced at a flow rate of 100L / h for oxidation, and at the same time, the outlet valve at the bottom of the reactor 1 is opened, and the diaphragm pump (pressure 0.6MPa) is turned on. The slurry is continuously pumped out by the diaphragm pump and returned to the top of the reactor 1 through the PPR pipeline for circulation. The slurry's own circulation improves the flow and mixing effect of the slurry and avoids the agglomeration of particles under low stirring conditions. After 30 minutes, the color of the slurry changes from white to light yellow, and the oxygen concentration in the dissolved oxygen meter rises from 0% to 3%. Compared with the colorimetric card ( Figure 2 ) After determining that the oxidation degree reaches the requirement, the oxidation and circulating material are stopped, and the growth rate of the detected particle size is curbed. In order to avoid misjudgment, in other embodiments, the slurry taken out can also be filtered and washed, and then dried at 100-120°C for 10-20 minutes, and the dried powder is taken for particle size analysis. After high-temperature drying, the soft agglomeration basically disappears, and the particle size distribution at this time is closer to its true value.

[0041] S4: After the particles are treated to suppress agglomeration, they are precipitated. After 6 hours of precipitation, the particle size D50 reaches 4.03 μm. Reactor 1 stops feeding, and high-power Prussian blue materials are obtained after washing and drying. The particle size distribution is unimodal, with a particle size span of 0.96 and a BET of 8.3 μm. 2 / g.

[0042] This embodiment also provides the use of the high-power Prussian blue material prepared by the above-mentioned high-power Prussian blue material preparation method in the preparation of a sodium ion battery.

[0043] Comparative Example 1:

[0044] Comparative Example 1 uses the same process as Example 1 for precipitation, except that no process adjustment (particle agglomeration inhibition treatment) is performed during the process. The particle growth rate curve is as follows: Figure 1 As shown, after 3 hours of precipitation, the curves of Comparative Example 1 and Example 1 show a large difference. After 6 hours of precipitation, the particle size is detected to be 5.82 μm and the feeding is stopped. After washing and drying, the product of Comparative Example 1 is obtained. Figures 3 to 5 As shown, the particles of Example 1 exhibit a more obvious dispersion effect, and the agglomeration between particles is significantly reduced compared with Comparative Example 1. The particle size span is reduced from 1.133 to 0.96. Figure 6 As shown, both Example 1 and Comparative Example 1 have rhombohedral phase structures, and no impurity peaks appear. The peak intensity of the highest peak (200) of Example 1 is 1451, which is higher than 1351 of the Comparative Example, indicating that the crystallinity of the monodisperse particles is better and the defects are fewer. The specific surface areas of Example 1 and Comparative Example 1 tested by BET are 8.3 m 2 / g,5.9m 2 / g, indicating that the exposed area of ​​the dispersed single crystal particles is larger, which will help to exert the rate performance of the material.

[0045] The Prussian blue positive electrode materials prepared in Example 1 and Comparative Example 1 were weighed in a mass ratio of Prussian blue: carbon black (Super-P): PVDF = 85:10:5, and NMP solvent was added to prepare a slurry with a suitable viscosity. 2 The amount of the electrode was evenly coated on the aluminum foil, and then after roller pressing and vacuum drying at 130°C for 12 hours, it was cut into electrodes with a diameter of 10 mm. The above-prepared electrode was assembled into a 2016 button half-cell, the separator was GF / D (purchased from Duoduo Reagent), the counter electrode was a sodium sheet (purchased from Duoduo Reagent), the electrolyte was 1M NaPF6, and the volume ratio was 1:1 EC / DEC+5% FEC. The assembled half-cell was charged and discharged at 10C (1500mA / g), and the charge and discharge range was 2-4.2V. From Figure 7 It can be seen that the half-cell assembled from the Prussian blue gradient positive electrode material synthesized in Example 1 has a discharge capacity of 123.4 mAh / g at a rate of 10C and a coulombic efficiency of 99.0%, while the first-cycle capacity of Comparative Example 1 is only 113.4 mAh / g and the coulombic efficiency is 98.9%, indicating that the gram capacity of the monodisperse material at a high rate is better than that of the conventional material.

[0046] Embodiment 2:

[0047] The method for preparing a high-power Prussian blue material provided in this embodiment comprises the following steps:

[0048] S1: Prepare a sodium ferrocyanide aqueous solution ((Na4Fe(CN)6)) with a molar concentration of 0.3 mol / L as raw material A, the temperature of raw material A is 20°C, and prepare a manganese sulfate solution (MnSO4) with a molar concentration of 0.4 mol / L as raw material B.

[0049] S2: Add 100L ultrapure water and 30Kg trisodium citrate complexing agent to the 1000L reactor 1 as the base liquid, the base liquid temperature is 30℃, and add 0.1% hexadecyl trimethyl ammonium bromide as a dispersant. Hexadecyl trimethyl ammonium bromide includes hydrophilic groups and hydrophobic groups. The hydrophilic group is adsorbed on the surface of the powder, and the hydrophobic chain extends into the solvent, preventing secondary agglomeration between particles through the steric hindrance effect. The precipitation synthesis temperature is controlled at 15℃ by a chiller. Nitrogen is introduced into the reactor 1. After 6h, raw materials A and raw materials B are continuously added to the base liquid respectively. The feed rates of raw materials A and raw materials B are both 40L / h, and stirred and mixed to form a precipitate. During the 0-1h of the precipitation reaction, the stirring speed is 350rpm. After 1h of the precipitation reaction, the stirring speed is reduced to 250rpm.

[0050] like Figure 8 As shown, the reactor 1 has an agitator 2, the number of stirring paddle layers of the agitator 2 is 3, the stirring blade 3 is a paddle blade with an inclination angle of 45°, and the length-to-diameter ratio of the stirring blade 3 is 8. The reactor 1 has a guide tube 4 inside, which is sleeved on the outside of the stirring paddle, and the stirring blade 3 of the lowest layer is flush with the bottom of the guide tube 4. The bottom of the reactor 1 is in an arc shape, and a protrusion 5 is provided at the center of the bottom wall of the reactor 1.

[0051] S3: Laser particle size distribution detection is performed every hour during the precipitation process. Zeta potential can be used to determine the degree of resistance to aggregation between particles in the precipitation system. When the zeta potential is between -25mV and -30mV, the particles begin to become unstable and tend to clump together. At this time, corresponding measures need to be taken to inhibit agglomeration. When the zeta potential is less than -45mV, the dispersion between particles is good and secondary agglomeration is not easy to occur. When the zeta potential is detected to rise to -26mV after 4h of precipitation, the particles are treated to inhibit agglomeration. Specifically, a 10% liquid alkali solution is introduced at a rate of 1L / h, and the slurry pH in reactor 1 is increased to 7.8 through online pH detection. The zeta potential becomes -53mV, and the introduction of liquid alkali is stopped at this time. If the pH exceeds 8.0, the surface morphology of the particles will be destroyed and hydroxide impurities will be generated.

[0052] S4: After the particles are treated to suppress agglomeration, precipitation treatment is continued. After 8 hours of precipitation, the solid content exceeds 10%. At this time, the overflow valve of reactor 1 is opened to discharge part of the slurry and solid-liquid separation and concentration treatment is performed on it. The separated mother liquor is returned to reactor 1 through a diaphragm pump, thereby diluting the solid content to 8%. The precipitation is continued until the reaction time is 10 hours. The particle size of the Prussian blue material is detected to be D50=5.08μm, reaching the required particle size, and the solid content is 9.2%. Reactor 1 stops feeding and the reaction stops. The material in reactor 1 is aged for 6 hours. Nitrogen is introduced during the aging process and the material is circulated through a diaphragm pump, and then washed and dried to obtain a high-power Prussian blue material with a specific surface area of ​​4.2m 3 / g.

[0053] Comparative Example 2:

[0054] Comparative Example 2 adopts the same process as Example 2, but no process adjustment is performed in the intermediate process (particle agglomeration inhibition treatment is performed). The final product D50 = 6.30 μm, and the specific surface area is 2.8 m 3 / g. The electron microscopy of the final products of Example 2 and Comparative Example 2 is as follows Fig. 9 and Fig.10 As shown in the figure, it can be seen that the cubic particles obtained by the method of Example 2 have clear edges and corners, and there is no obvious clustering between the particles, while the single crystal particles of Comparative Example 2 are disorderly stacked together and difficult to disperse. The dispersion of the material obtained in Example 1 is significantly better than that of Comparative Example 2.

[0055] Embodiment 3:

[0056] The high-power Prussian blue material obtained in Example 2 was dried and then subjected to air flow crushing to further open the particles that were bonded together, and to remove some fine powder through a cyclone separator, thereby obtaining a single crystal material with a further narrowed particle size. The classification frequency of the air flow crushing was 30 Hz, the crushing pressure was 0.4 MPa, and the particle size distribution before and after crushing was as shown in the figure. Fig.11 As shown in the figure. After air flow crushing, D50 dropped from 5.84μm to 5.54μm, and the span decreased from 1.102 to 0.96, indicating that the distribution of particles was further narrowed. The specific surface area increased from 8.9m 3 / g rises to 9.4m 3 / g.

[0057] Comparative Example 3:

[0058] The crushing pressure used was 1.4 MPa. The crushing was excessive, and the obtained single crystal particles increased in fine powder, and the particle size distribution showed a bimodal distribution. The D50 dropped to 3.34 μm, and the span increased to 1.133. Figure 12 to Figure 13 As shown, the crushing process did not achieve the expected effect, and excessive fine powder would deteriorate the electrical properties of the material.

[0059] The chemical formula of the high-power Prussian blue material prepared in Example 3 is Na 1.76 MnFe(CN)6 was assembled into a 300mAh sodium ion soft pack battery. The full battery pole piece and assembly process were as follows: The prepared Prussian blue derivative positive electrode material was Prussian blue: carbon black (Super-P): PVDF = 90:6:4. Each raw material was weighed and NMP solvent was added to prepare a slurry with a suitable viscosity. The slurry was stirred at 8 mg / cm 2 The amount of the material was evenly coated on the aluminum foil, and then after roller pressing and vacuum drying at 130°C for 24 hours, it was cut into 41*76mm positive electrode sheets; the negative electrode material was weighed according to the mass ratio of hard carbon: carbon black (Super-P): PVDF = 94:4:2, and the raw materials were weighed according to 3mg / cm 2 It is evenly coated on aluminum foil in an amount of , and then after roller pressing and vacuum drying at 130°C for 24 hours, it is cut into negative electrode sheets of 41.5*76.5mm in size.

[0060] The above-prepared electrode stacking process was assembled into a soft pack battery, the separator was PE (purchased from Duoduo Reagent), the electrolyte was 1M NaPF6, and the volume ratio was 1:1 EC / DEC+5% FEC (purchased from Duoduo Reagent). The soft pack battery assembled in this example was charged at 1C (0.3A), and discharged at 1C and 60C (18A), with a charge and discharge range of 2.6-3.6V. The results are as follows Fig.14 As shown in the figure, it can be seen that the soft-pack battery assembled from the Prussian blue positive electrode material prepared in Example 3 has a discharge capacity of 288.6 mAh at 1C rate and a capacity of 201.9 mAh at 60C rate. Although the polarization increases at high rates, it can still maintain 70.0% of the capacity at 1C, indicating that the full battery prepared from high-power materials has excellent rate discharge capability.

[0061] The present invention strengthens and optimizes the dispersion, mixing and shearing effects of the stirring equipment during the precipitation process, regulates the number of nuclei and surface charge adsorption during the precipitation synthesis process, and ages and crushes the materials after the synthesis, thereby obtaining a Prussian blue positive electrode material with uniform dispersion between primary particles, reduced secondary agglomeration between particles, and narrow particle size distribution. In the production amplification, monodisperse narrow particle size distribution particles consistent with the physical and chemical properties of the pilot test are obtained, laying a foundation for the large-scale application of high-power Prussian blue. The sodium ion battery assembled with the obtained high-power Prussian blue material as the positive electrode material can achieve a discharge rate of ≥60C, and the capacity retention rate is more than 70% at a 1C rate. The controlled crystallization precipitation method is used to synthesize Prussian blue particles with monodisperse narrow particle size distribution, the number of secondary agglomerates between particles is reduced, the specific surface area of ​​the material is improved, thereby shortening the diffusion path of sodium ions from the surface of the particles to the inside, increasing the contact area between the material surface and the sodium ion electrolyte, and improving the ultra-high rate discharge capacity of the sodium ion battery, which is superior to the traditional agglomerated positive electrode material. During the synthesis process, the particle agglomeration situation can be quantitatively determined in real time by rapid detection methods such as the color control of the slurry in the reactor 1, the distinction between soft and hard agglomeration of particles, the particle size growth rate curve, and zeta potential analysis, so as to adjust and optimize the precipitation process in time. These control processes and detection methods can also be extended to the synthesis process of other monodisperse battery material systems.

[0062] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, it should be understood by those skilled in the art that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features thereof may be replaced by equivalents. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a high-power Prussian blue material, characterized in that: The following steps are involved: S1: preparing a solution including ferrocyanide as raw material A, and preparing a solution including a transition metal salt as raw material B; S2: Add the base liquid into the container, introduce nitrogen into the container, and after 2-6 hours, continue to add raw material A and raw material B into the base liquid, and stir and mix to form a precipitate; S3: Laser particle size distribution detection during the precipitation process; A particle growth rate curve is made according to the detected particle size distribution D50 value. When the curve has an upward inflection point and the slope is greater than 1; Or perform zeta potential detection, when the zeta potential is between -25mV and -30mV; Carry out particle agglomeration inhibition treatment; S4: After the particles are subjected to the agglomeration suppression treatment, the precipitation treatment is continued until the particle size distribution D50 is detected to be 1.0-6.0 μm, and the feeding is stopped. After washing and drying, a high-power Prussian blue material is obtained.

2. The method for preparing a high-power Prussian blue material according to claim 1, characterized in that: The particle size distribution of the high-power Prussian blue material is D50=1.0-6.0 μm, the particle size distribution is unimodal, the particle size span is ≤1.20, and BET is ≥2.0 μm. 2 / g.

3. The method for preparing a high-power Prussian blue material according to claim 1, characterized in that: Raw material A includes at least one of a sodium ferrocyanide aqueous solution, a potassium ferrocyanide aqueous solution, and a lithium ferrocyanide aqueous solution, with a molar concentration of 0.1-1 mol / L, and a temperature of raw material A of 20-60° C.; Raw material B includes one or more mixed solutions of sulfates of manganese, iron, cobalt, nickel, zinc and copper, with a molar concentration of 0.1-3 mol / L; The base liquid is an aqueous solution, a sodium sulfate solution or a sodium chloride solution, the mass concentration of the sodium sulfate solution or the sodium chloride solution is 100-300 g / L, and the base liquid temperature is 0°C-40°C; The base solution also includes a complexing agent with a mass concentration of 30-300 g / L; The complexing agent is at least one of trisodium citrate, ammonia water, sodium oxalate, sodium phosphate, sodium pyrophosphate, sodium acetate, ethylenediaminetetraacetic acid, disodium ethylenediaminetetraacetate, sodium manganese ethylenediaminetetraacetate, triethanolethylenediamine, urea, sodium succinate, sodium tartrate, polyvinylpyrrolidone, and polyacrylamine; In step S2, after adding the base liquid into the container, an inorganic dispersant or an organic surfactant dispersant containing sodium ions is added into the base liquid, and the amount of the dispersant added is 0.02-1% of the mass of the base liquid; The inorganic dispersant containing sodium ions is at least one of sodium silicate, sodium tripolyphosphate, sodium hexametaphosphate, sodium pyrophosphate and sodium aluminate; The organic surfactant dispersant is at least one of long-chain fatty acids, hexadecyltrimethylammonium bromide, triethylhexyl phosphoric acid, sodium lauryl sulfate, methylpentyl alcohol, polyacrylamide, fatty acid polyethylene glycol ester, and polyether siloxane.

4. The method for preparing a high-power Prussian blue material according to claim 1, characterized in that: The container in step S2 is a reactor, and the volume of the reactor is greater than 300L; The reactor has a stirrer, wherein the stirring paddles of the stirrer have a number of ≥2 layers, the stirring blades are paddle-type or propeller-type blades with an inclination angle of >30°, and the length-to-diameter ratio of the stirring blades is >5; The reactor is provided with a guide tube inside, the guide tube is sleeved on the outside of the stirring paddle, and the stirring paddle at the bottom is flush with the bottom of the guide tube; The bottom of the reactor is in an arc shape, and a protrusion is provided at the center of the bottom wall of the reactor; The motor power of the stirrer is greater than 60kw, and the maximum speed of the stirring paddle is greater than 200rpm; The time for raw material A, raw material B, and base liquid to be evenly mixed in the reactor is less than 1s; The feed rate of raw material A and raw material B is 40-200 L / h.

5. The method for preparing a high-power Prussian blue material according to claim 1, characterized in that: In the precipitation reaction, the precipitation synthesis temperature is 0-40°C, the solid content is 0-10%, and the precipitation cycle is 3-12h; During the 0-1h of precipitation reaction, the stirring linear velocity is greater than 500cm / s, and after 1h of precipitation reaction, the stirring linear velocity is less than 500cm / s; After 1 hour of precipitation reaction, the particle size is controlled at 20-30% of the target particle size. If the particle size is less than 20% of the target particle size, part of the slurry is immediately discharged; During the precipitation reaction, when the solid content is greater than 10%, part of the slurry is discharged and concentrated, and the obtained concentrated liquid is returned to the container for dilution to reduce the solid content.

6. The method for preparing a high-power Prussian blue material according to claim 1, characterized in that: Before laser particle size distribution testing, the slurry is removed from the container; The taken-out slurry is subjected to ultrasonic treatment for 5-8 minutes, with an ultrasonic power of 20-100 KHz; Alternatively, the taken out slurry is filtered and washed, and then air-dried at 100-120°C for 10-20 minutes.

7. The method for preparing a high-power Prussian blue material according to claim 1, characterized in that: In step S3, a particle growth rate curve is prepared with the precipitation time as the horizontal axis and the particle volume change as the vertical axis; The formula for calculating the change in particle volume between the n+1 hour and the n hour is: [(D50(n+1) / 2) 3 -(D50(n) / 2) 3 ] / [(n+1)-n]。 8. The method for preparing a high-power Prussian blue material according to claim 1, characterized in that: The particle agglomeration inhibition treatment includes at least one of oxidation treatment of the particle surface, increasing the pH value of the precipitation process, and circulating treatment of the slurry; In step S4, the slurry is aged after the feeding is stopped, nitrogen is introduced during the aging process and the slurry is circulated. After aging for 4-8 hours, the slurry is washed and dried to obtain a high-power Prussian blue material. The method also includes performing air flow crushing on the high-power Prussian blue material obtained in step S4, wherein the classification frequency of the air flow crushing is 25-40 Hz and the crushing pressure is 0.3-1.2 Mpa.

9. The method for preparing a high-power Prussian blue material according to claim 8, characterized in that: The oxidation treatment of the particle surface includes introducing compressed air, pure oxygen or hydrogen peroxide into the container at a flow rate of 100-300 L / h and an oxidation time of 10-120 min; Increasing the pH value of the precipitation process includes adding at least one of sodium hydroxide, sodium carbonate, sodium oxalate, potassium hydroxide, potassium hydroxide, and potassium oxalate to the container to control the pH value at 7.5-8.0; The slurry circulation treatment includes continuously discharging the slurry from the bottom of the container and continuously sending the discharged slurry into the container from the top of the container through a diaphragm pump, and the pressure of the diaphragm pump is 0.1-0.8MPa.

10. Use of the high-power Prussian blue material prepared by the method for preparing a high-power Prussian blue material according to any one of claims 1 to 9 in preparing a sodium ion battery.